Synthesis of Problems in Utilizing Regional Incentive Funds (RIF) during COVID-19 Pandemic in Indonesia - Andi Setyo Pambudi (TRANSFORMASI: Jurnal Manajemen Pemerintahan, 2023)
Abstract The implementation of Fiscal Decentralization is expected to significantly affect the dynamics of regional development and economic performance, regarding the central government transfer to various zones through RIF (Regional Incentive Funds). These funds are optimal during COVID-19 pandemic when the financial capacity for the development of the country is directed more evenly with the desires of several regions, to develop areas with diverse potential. This pragmatically explains that the implementation of RIF varies greatly regarding utilization and challenges. Therefore, this study aims to analyze the implementation of RIF in the best regions of Regional Development Award (RDA) based on good planning documents. In this context, the field issues related to the use of RIF were interesting topics to be discussed. COVID-19 pandemic was also a concern in the implementation of the development funded by transfer funds, considering that when planned, RIF did not anticipate the non-natural disaster. From this description, RDA was a form of competition where the winners obtained RIF reward. Subsequently, this study presented synthesis regarding the realization and effectiveness of using RIF budget in the best regions of RDA in 2020. It also obtained information on field issues and provided a basis or input for better overall RIF planning. In this study, the analytical method combined a literature review of Regional Government reports, journals, and a Focus Group Discussion (FGD). This involved 9 Regional Development Planning Agencies, which obtained RIF in the planning category. The results showed that Regional Government effectively used RIF as one of funding instruments for COVID-19. However, some common challenges were observed, such as the absence of measurable targets, an unclear technical guide, slow implementation due to the LSSR (Large-Scale Social Restrictions), and the lack of an integrated supervision mechanism. Keywords: Transfer Funds; RIF; Evaluation; RDA Abstrak Pelaksanaan Desentralisasi Fiskal dalam bentuk transfer dana pusat ke daerah melalui Dana Insentif Daerah (DID) diharapkan oleh pemerintah memberi pengaruh signifikan terhadap dinamika pembangunan daerah yang pada gilirannya berdampak pada kinerja perekonomian. Dana ini akan optimal pada masa Pandemi COVID-19 ketika kemampuan finansial negara bagi pembangunan diarahkan lebih merata selaras dengan keinginan daerah dalam upaya pengembangan wilayah dengan potensi yang beragam. Pada praktiknya implementasi dana insentif sangat bervariasi, baik pemanfaatan maupun permasalahannya. Penelitian ini mencoba memotret pelaksanaan DID pada daerah terbaik Penghargaan Pembangunan Daerah (PPD) yang terpilih berbasis dokumen perencanaan yang baik. Permasalahan lapangan terkait pemanfaatan DID menjadi hal yang menarik diulas. Pandemi COVID-19 menjadi perhatian dalam pelaksanaan pembangunan yang didanai dana transfer mengingat saat direncanakan, DID 2020 belum memprediksi adanya bencana non alam ini. Perlu diketahui, Penghargaan Pembangunan Daerah (PPD) adalah salah satu bentuk kompetisi yang pemenangnya mendapatkan reward DID. Penelitian ini bertujuan untuk menyajikan sintesis realisasi dan efektivitas pemanfaatan anggaran DID kepada daerah terbaik PPD tahun 2020, mendapatkan informasi permasalahan lapangan, serta dijadikan landasan atau masukan dalam perencanaan DID secara umum yang lebih baik. Metode analisis menggunakan kombinasi literature review dari laporan pemda, jurnal, dan Focus Group Discussion (FGD) yang melibatkan sembilan Bappeda yang mendapatkan DID dari kategori perencanaan. Hasil analisis menunjukkan sintesis bahwa DID telah digunakan Pemda sebagai salah satu instrumen pendanaan COVID-19 yang efektif dengan kendala umum terkait tidak adanya target terukur, belum jelasnya juknis, lambatnya implementasi karena PSBB, serta belum adanya mekanisme pengawasan yang terintegrasi. Kata kunci: Dana Transfer; DID; Evaluasi; PPD